Preparation and calorimetry characterization of nitrogen-enriched activated carbons and their application in the removal of carbon dioxide - Vargas-Delgadillo, Diana Paola; Giraldo, Liliana; Moreno-Pirajan, Juan Carlos (European Journal of Chemistry, 2017)
This paper reports the preparation and characterization of granular carbon materials those were prepared using chemical activation of African palm stone with ZnCl2 and then chemically modified in order to increase the nitrogen content. Functionalization processes with activated carbons, modify their textural and chemical characteristics, this fact was observed using N2 adsorption at 77 K, Boehm titration, infrared Spectroscopy using immersion calorimeter in liquids with different chemical nature (H2O, C6H6, NaOH and HCl). The results show that the solids obtained have BET surface area and pore volume up to 1200 m2/g and 0.44 cm3/g, respectively. Immersion enthalpies of samples are between -9.87 and 141.9 J/g. The results show that with the process of functionalization employed in this work, increasing in the nitrogen content and the modification of the adsorbents surface is achieved. Finally, we found that with this activation and modification procedure, the activated carbons produced have a CO2 adsorption capacity until 174 mg CO2 /g.